3D coronary MR angiography at 1.5 T: Volume‐targeted versus whole‐heart acquisition. Issue 3 (31st January 2013) - Jin, Hang; Zeng, Meng‐Su; Ge, Mei‐Ying; Yun, Hong; Yang, Shan
<x xml:space="preserve">Abstract</x> Purpose: To compare volume‐targeted acquisition with whole‐heart acquisition in 1.5‐T free‐breathing 3D coronary magnetic resonance angiography (MRA) with parallel imaging. Materials and Methods: The major coronary arteries were imaged in 36 subjects using the whole‐heart and volume‐targeted acquisitions with comparable imaging parameters. The quantitative and semiquantitative data derived from these two acquisition methods were analyzed statistically, with P < 0.05 considered significant. Results: Both the right coronary artery (RCA) / left circumflex artery (LCX)‐ and the left main (LM) / left anterior descending (LAD)‐targeted acquisitions had similar results in navigator efficiencies and apparent signal‐to‐noise ratio (SNR) in comparison with whole‐heart acquisition. Apparent contrast‐to‐noise ratio (CNR) of the volume‐targeted imaging was significantly higher than that of the whole‐heart imaging. The imaging time required for a whole‐heart scan was significantly longer than each of the RCA/LCX‐ and LM/LAD‐targeted acquisitions. However, the sum of scanning times derived from volume‐targeted imaging was significantly longer than that of whole‐heart acquisition. Both RCA/LCX‐ and LM/LAD‐targeted acquisition yield higher vessel sharpness and overall image quality in comparison with whole‐heart acquisition. The lengths of the major coronary arteries were not significantly different for the whole‐heart and volume‐targeted approaches. The whole‐heart method was obviously superior to the volume‐targeted method in terms of visualization of the posterior descending artery. Conclusion: For current 1.5‐T navigator coronary MRA, volume‐targeted and whole‐heart acquisitions have their own advantages and the choice of methods may vary in accordance with the different aims of clinical practice. J. Magn. Reson. Imaging 2013;38:594–602. © 2013 Wiley Periodicals, Inc.